Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Effectiveness of rodents as local seed dispersers of Holm oaks. - Gómez, José M; Puerta-Piñero, Carolina; Schupp, Eugene W (Oecologia, 2008)
In this study we assessed the effectiveness of rodents as dispersers of Quercus ilex in a patchy landscape in southeastern Spain. We experimentally followed the fates of 3,200 marked and weighed acorns from dispersal through the time of seedling emergence over three years. Rodents handled about 99% of acorns, and dispersed 67% and cached 7.4% of the dispersed acorns. Most caches were recovered and consumed, and only 1.3% of the original experimental acorns were found alive in caches the following spring. Dispersal distances were short (mean = 356.2 cm, median = 157 cm) and strongly right-skewed. Heavier acorns were dispersed further and were more likely to be cached and survive than lighter acorns. All caches were in litter or soil, and each contained a single acorn. Rodents moved acorns nonrandomly, mostly to oaks and pines. Most surviving acorns were either in oaks, a poor microhabitat for oak recruitment, or shrubs, a suitable microhabitat for oak recruitment. Our results suggest that rodents, by burying a relatively high proportion of acorns singly in shrubs and pines, act as moderately effective dispersers of Q. ilex. Nonetheless, this dispersal comes at a very heavy cost.
Keywords: Animals; Ecosystem; Feeding Behavior; germination; Germination: physiology; Quercus; Quercus: physiology; Rodentia; Rodentia: psychology; Seeds; Seeds: physiology; Soil; Spain